Development Strategy of Village-Owned Enterprises (Bumdes) Case Study at Bumdes Amanah Rakyat Wonoharjo Village, Girimulya District - Mita Agustina; Romi Gunawan (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to determine alternative strategies in the development of Amanah Rakyat BUMDes by identifying internal factors and external factors that can affect Amanah Rakyat BUMDes. The method used is descriptive with a sampling technique, namely purposive sampling. The data collection technique used was through interviews with the management of bumdes and the people of Wonoharjo Village. The business development strategy of BUMDes Amanah Rakyat is obtained from the results of SWOT analysis which is prepared using the SWOT matrix. The results of this analysis are sourced from the Stength and Treath Strategy, namely Optimizing facilities and infrastructure to improve good services, developing businesses that are run so as not to be left with competitors, ensuring continuity of business fields that are being run.